Pharmacognostical and Physiochemical Parameters of Trachyspermum ammi (L.) Sprague (Fruits) - Baby Chauhan; Gopal Kumar; Mohammed Ali (Current Research in Pharmaceutical Sciences, 2013)
Trachyspermum ammi (L.) Sprague, syn. Carum copticum Benth. et Hook., commonly known as ajwain or Bishop’s weeds; belongs to the family 'Apiaceae'. its fruits yielded 2% to 4% brownish essential oil, with thymol as the major constituent (35% to 60%).The present study deals with the Pharmacognostical examinations like morphological and histological characters of fruits of T. ammi besides physiochemical, fluorescence and phytochemical analysis. The HPTLC fingerprintings of T. ammi (fruits) petroleum ether, dichloromethane, chloroform, methanol, ethanol extract developed in solvent system (toluene: ethylacetate; 93:7) and spotted thymol peaks at UV 366 nm. These observations will enable to standardize the botanical identity of the drug in its crude form. Data evolved in this exploration could be used in laying down pharmacopoeial principles for the drug studied, as standardization of herbal medicines is completely essential.